Analysis of SDSS spectra and GALEX photometry with STARLIGHT: stellar populations and dust attenuation in local galaxies - Werle, Ariel (2019)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Ciências Físicas e Matemáticas, Programa de Pós-Graduação em Física, Florianópolis, 2019.